The potential public health impact of Herpes Zoster vaccination in the 65 years of age cohort in Italy. Issue 2 (1st February 2020) - Volpi, Antonio; Boccalini, Sara; Dari, Silvia; Clarke, Christopher; Curran, Desmond; Loiacono, Idalba; Pitrelli, Andrea; Puggina, Anna; Tosatto, Roberta; Van Oorschot, Desirée; Franco, Elisabetta
ABSTRACT: Herpes Zoster (HZ) presents a considerable public health burden in Italy among people aged ≥50 years. This study aimed to assess the clinical and economic impact of HZ vaccination in the 65 years of age (YOA) cohort in Italy, by comparing the new Adjuvanted Recombinant Zoster Vaccine (RZV) with the currently available Zoster Vaccine Live (ZVL). A static Markov model was developed to follow all 65 YOA subjects from the year of vaccination over their lifetime by comparing three different HZ vaccination strategies: no vaccination, vaccination with ZVL and vaccination with RZV. In the base-case scenario, three 65 YOA cohorts were assumed to be vaccinated within three years, with a vaccine coverage rate of 20%, 35% and 50% at Year 1, 2 and 3 respectively, as recommended by the National Immunization Plan. The three 65 YOA Italian cohorts accounted altogether for 2, 290, 340 individuals. Of these, it was assumed that 564, 178 subjects could be vaccinated with either RZV or ZVL in three years. The vaccination with RZV could prevent an additional total number of 35, 834 HZ and 8, 131 postherpetic neuralgia (PHN) cases over ZVL, leading to additional total savings of €12.4 million for the national healthcare and social systems. The introduction of RZV can be expected to have higher impact on the burden of HZ disease in the 65 YOA cohort in Italy. The avoided HZ and PHN cases can lead to an associated reduction in economic burden to the healthcare and social systems.